Introducing neorate: a revolutionary heart rate assessment training suite - Mohamed, Mohamed Ismat Abdelhamid; Okhiria, Peter Emuata; Tamakloe, Christian Kojo (2014)
This report explains the technical aspects of our project, which aims to develop and commercialize the mobile application NeoRate, to train neonatal doctors for more effective and efficient heart rate assessment techniques to be used during newborn resuscitation. The first chapter analyzes the problem and our proposed solution, and provides strong evidence based on the results of published medical journals. There is clearly a problem with the techniques currently used in newborn heart rate assessment during resuscitation. Our proposed solution is a mobile application that will enable the users to practice different heart rate assessment techniques including our proposed “Six Second Technique”, in a simulated environment, by listening to randomly generated newborn heart rate sounds. A little background regarding newborn resuscitation is then provided in the second chapter. The American Newborn Resuscitation Algorithm is explained which is an internationally accepted guideline for newborn resuscitation in which the doctors repeatedly assess the newborn’s heart rate in 30 second intervals and proceed with different actions based on the assessment result.. It emphasizes the need for both an effective and efficient heart rate assessment technique. The third chapter sheds some light on the currently adopted heart rate assessment techniques. It compares the electronic and manual techniques and ends with a brief discussion about mobile applications. This is followed by a detailed analysis of the design and implementation of the application in the fourth chapter. Beginning with an overview, it proceeds to describe the tools and processes used during this stage and examines the structure of the application at source code level. The fifth chapter of this report is concerned with the usability test we conducted. It begins with a brief introduction about the usability standards that we used in our study, and explains the method we used to evaluate the usability of our application. The feedback we received form the users is then summarized and discussed in detail along with the remarks and suggestions.